Discovery of Potent EGFR Inhibitors With 6-Arylureido-4-anilinoquinazoline Derivatives - Li, Meng; Xue, Na; Liu, Xingang; Wang, Qiaoyun; Yan, Hongyi; Liu, Yifan; Wang, Lei; Shi, Xiaowei; Cao, Deying; Zhang, Kai; Zhang, Yang (Frontiers in Pharmacology, 2021)
According to classical pharmacophore fusion strategy, a series of 6-arylureido-4-anilinoquinazoline derivatives (Compounds 7a-t) were designed, synthesized, and biologically evaluated by standard CCK-8 method, induction apoptosis assay, and enzyme inhibition test. Among the title compounds, Compound 7a, 7c, 7d, 7f, 7i, 7o, 7p, 7q exhibited promising antiproliferative bioactivities, especially Compound 7i with excellent antitumor activities against A549, HT-29 and MCF-7 cell lines (IC50 = 2.25, 1.72, and 2.81 μM, respectively) than those of Gefitinib and Erlotinib. In addition, the enzyme activity inhibition assay indicated that the synthetic compounds had sub-micromolar level (IC50, 11.66-867.1 nM), which was consistent with the tumor cell lines growth inhibition test. By comparing the binding mechanisms of Compound 7i (17.32 nM), Gefitinib (25.42 nM), and Erlotinib (33.25 nM) in EGFR, it could be found that Compound 7i could extend to the effective region with similar action conformation of Gefitinib, and interacted with the L85, D86, and R127, increasing the binding affinity of Compound 7i to EGFR. Through the combination of dominant fragments, 14 compounds with EGFR inhibitory activity were designed and synthesized, and the action mechanism was explored through computational approaches, providing valuable clues for the research of anti-tumor agents based on EGFR inhibitors.